Contact mechanics and friction processes in ultrasonic wire bonding - Basic theories and experimental investigations. (3rd March 2020) - Long, Yangyang; Twiefel, Jens; Wallaschek, Jörg
Abstract: Even though ultrasonic (US) wire bonding has been a popular interconnection technique in electronic packaging industry for decades, the contact and friction conditions during the bonding processes have not been well understood. In this work, the relative motion at the wire/substrate interface and the wire/tool interface, and the influences of oxides and microwelds on the friction at the wire/substrate interface are brought together to systematically and comprehensively analyze the contact and friction at the two interfaces. Specifically for the analysis at the wire/substrate interface, the contact was divided into three different areas where different oxide removal and microweld formation conditions exist. The theoretical analysis was then validated by real-time observations from both side and bottom view. Both analyses show that in the beginning stage, the tool and the wire are well coupled. The wire gross-slides on the substrate and the most substantial friction takes place in the inner peripheral region. The shift of the tool equilibrium position was experimentally observed during this stage. As the process goes on, the contact area between the wire and the substrate gets larger. Within the contact area, the oxide layer is broken into particles and then transported to the peripheral contact region. Microwelds are formed in the oxide-free areas. Sliding friction and microweld connections coexist at the wire/substrate interface. As more oxides are removed and more microwelds are formed, the relative displacement at the wire/substrate interface becomes smaller while the relative displacement at the wire/tool interface becomes larger. Finally, microwelds cover the majority of the contact. The understanding on the contact and friction during US wire bonding leads to a potential enhancement of the processes in industry production.